Sustainable Processing of Business Operations - Arshi Naim (Web of Journals Publishing, 2023)
In the current scenario, preserving the environment has become a vital and critical area of discussion and requires a concrete steps and solutions to be implemented. Organizational strategies for saving energy are currently largely defined by three main courses of action: From a process organization perspective, efforts are being made to optimize processes and invest into more energy efficient infra- structure; from a behavioral perspective, one-time interventions such as energy campaigns or feedback mechanisms are common means to reduce environmental impact. However, both approaches face limitations concerning the scope of intervention. We conducted action-based research regarding energy optimization practices in Business Process Management (BPM). We discovered a lack of integrated approaches as regards fostering sustainability in organizations and deriving strategies for bridging the gap between strategic planning and everyday work in order to manage sustainability strategies more effectively and efficiently in BPM. We proposed the best organizational policies to be applied for preserving the environment and attain profit goals for the firms by going green in BPM.
Keywords: Green Business Process Management, Organizational Strategies, Action Based Research